Audit committee attributes, audit quality and performance of oil and gas companies - Bako, Paul Matudi (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study examines the audit committee attributes, audit quality, and financial performance of listed oil and gas companies in Nigeria. Research methodology: Audit committee attributes were measured by audit committee size, audit committee independence, and audit committee financial expertise, and audit quality was measured by audit fees charged by an external auditor. Financial performance is measured in terms of earnings per share. The researcher used secondary data extracted from the ten listed oil and gas firms annual reports, and the accounts were analyzed using Panel Least Square. Results: This study reveals a positive and statistically significant relationship between audit committee independence and earnings per share. It also shows that audit quality moderates audit committee attributes significantly and increases firm performance. This study recommends that maintaining high audit quality within the audit committee is crucial for a firm if it aims to offer increased assurance to investors and stakeholders concerning the precision and dependability of its financial statements. Limitations: This study was limited to listed oil and gas companies in Nigeria ranging from to 2016-2022.   Contribution:  This study examined factors that can moderate the relationship between audit committees and the financial performance of listed oil and gas companies in Nigeria. One such factor is audit quality, which can potentially enhance or diminish the impact of audit committee effectiveness on financial performance. No study conducted in Nigeria has examined this relationship specifically in the oil and gas sector. This knowledge gap served as the rationale for conducting this study.